Welcome Jean-Luc Nancy - Sergio Benvenuto (EJP import test, 2021)
Summary: The author describes his personal relationship with the French philosopher Jean-Luc Nancy (who died in August 2021), based essentially on interviews, conversations and correspondence. And it is one of these published conversations that the author uses to illustrate Nancy’s philosophical relationship to those authors cited by Nancy himself as essential to philosophical modernity: Heidegger, Wittgenstein, Freud, Bataille and Derrida. In particular, the author highlights the dimension of the body as Leib and touch in Nancy’s philosophical journey.